2022
DOI: 10.3389/fcvm.2022.830062
|View full text |Cite
|
Sign up to set email alerts
|

Improving Left Atrial Appendage Occlusion Device Size Determination by Three-Dimensional Printing-Based Preprocedural Simulation

Abstract: BackgroundThe two-dimensional (2D)-based left atrial appendage (LAA) occluder (LAAO) size determination by using transesophageal echocardiography (TEE) is limited by the structural complexity and wide anatomical variation of the LAA.ObjectiveThis study aimed to assess the accuracy of the LAAO size determination by implantation simulation by using a three-dimensional (3D)-printed model compared with the conventional method based on TEE.MethodsWe retrospectively reviewed patients with anatomically and physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The support of numerical tools leads to an even more patient‐centric intervention and allows for improvement and prediction of procedural outcomes. In this light, positive impacts on the patient's health can be obtained 15–23 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The support of numerical tools leads to an even more patient‐centric intervention and allows for improvement and prediction of procedural outcomes. In this light, positive impacts on the patient's health can be obtained 15–23 …”
Section: Introductionmentioning
confidence: 99%
“…In this light, positive impacts on the patient's health can be obtained. [15][16][17][18][19][20][21][22][23] Namely, only two studies focusing on the device deployment phase are reported in the literature, given the fact that most of the computational investigations are devoted to the left atrium hemodynamics before, [24][25][26] or after the LAA closure. [27][28][29] As regards computational structural modeling of LAAO, the platform developed by FEOPS company (HEARTguide) based on finite element analyses (FEA) has been recognized as a medical device and suggested as a valid planning tool for comparing different possible LAAO procedures (i.e., positioning of the access/delivery system with respect to the LAA ostium) and selecting the most effective in terms of safe outcomes (no DP into the atrium, good device apposition on the LAA wall and complete LAA occlusion).…”
mentioning
confidence: 99%
“…William D. Kim, Iksung Cho et al. retrospectively analyzed 28 cases of percutaneous LAA occlusion and concluded that the LAAO size determination by using simulation with 3D‐printed models of the LA showed improved accuracy compared with conventional methods based on 2D transesophageal echocardiography (TEE) 5 . Through rehearsal simulations of 10 patients using the phantom, Dayeong Hong, Sojin Moon et al.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptation of 3D printing in clinical care and procedural planning has already demonstrated a reduction in early operator learning curve or in centers without previous experience on transcatheter interventions[ 2 , 15 - 17 ]. Several studies have evaluated the added value of 3D-printed models for training and planning of LAAO interventions[ 18 ]. However, Conti et al .…”
Section: Introductionmentioning
confidence: 99%